(untitled) (Global Journal of Human-Social Science, 2010)
This paper discusses the bearing of the Primordial Institutions of caste and Patriarchy on the emerging women’s leadership in local self-Government in Uttarakhand. The state of Uttarakhand was established in the year 2000 dated 9 Nov. The introducing of reservation for the women in local self-Government for the first time in the country, has also led to make similar provisions in the Uttarakhand Panchayati Raj Act, 2003 following the 73 rd constitution Amendment in relation to Panchayati Raj Act, 1992 in the constitution of India. This has enabled larger participation of women of deprived sections of our society in local self-governance. However, the caste and patriarchy have larger implication in the emergence and performance of women leaders at the gross root level. This paper is based on the women leaders who hail from the lower stratum of the society who are more democratic and people centered, whereas those people from the upper caste are more conservative and family centered. The lower caste women leaders outnumber their male counterparts in the panchayats which provides explanations for the presence have more than one third women elected members in panchayats. The paper is based on the fieldwork carried out in the Almora and Pithoragarh district of Uttarakhand during 2003-2008.